The integration of supply chain coordination in higher education supply chain framework - Ahmed Waham, Mohammed; Lestari, Fitra (International Business Education Journal, 2019)
The purpose of this conceptual paper is to develop the education supply chain framework by integrating the supply chain coordination dimensions that are information sharing, commitment, joint decision making and responsiveness. A qualitative framework analysis methodology proposed by Srivastava and Thomson (2009) will be performed by interviewing seven groups of supply chain actors (schools/polytechnics, university, employers, government, professional bodies, current students and alumni) until data saturation is reached to understand the participants’ experiences about supply chain coordination. The interview data will be analysed by using thematic analysis and emerging themes will help to explain the education supply chain framework from supply chain coordination perspectives. In education supply chain context, this is the first attempt to embed the selected supply chain coordination dimensions in the existing framework. Education supply chain actors could benefit from this framework by performing better coordination to reduce the education-job mismatch.